Coffee agroforestry systems capable of reducing disease-induced yield and economic losses while providing multiple ecosystem services - Cerda Bustillos, Rolando (2020)
Crop losses caused by pests and diseases decrease the incomes and threaten the livelihoods of thousands of families worldwide.During two years, in a research network of 61 coffee plots under a wide variety of shade and management conditions in Turrialba, Costa Rica, we quantified primary and secondary coffee losses (yield and economic losses) and indicators of three other ecosystem services: provisioning of agroforestry products (bananas, plantains, other fruits, and timber), maintenance of soil fertility and carbon sequestration. We then performed an analysis of the relationships between losses and ecosystem service indicators. Our results suggest that the regulation of diseases and associated losses in agroforestry systems should be based on, and take advantage of, the positive effects of plant biodiversity, adequate shade cover, good soil fertility, and minimal use of fungicides.